Nursing Management Ethics From The Perspective Of Islamic Values - Muhammad Aghna Firdaus Subagja; Desyana Rahmah Arundina; Nabilla Rizky Velly; Najwa Syifa Amalia; Rachel Nazwa Sunardita Kusnadi; Ratika Jawi Lestari; Tedi Supriadi; Akhmad Faozi (Universitas Pahlawan Tuanku Tambusai, 2026)
Nursing management currently faces a distinct gap between professional ethical standards and field practices due to administrative pressures, resource limitations, and a lack of spiritual value integration, which ultimately decreases healthcare service quality and patient safety. This study aims to explore the application of nursing management ethics from an Islamic perspective to improve healthcare service quality. Employing a qualitative approach with an in-depth interview design, data were gathered from Nahdlatul Ulama (NU) figures and professional nurses in Sumedang Regency, supported by a literature review from 2017 to 2026. The results indicate that the integration of Islamic values (amanah, ṣidq, 'adl, rahmah, and ihsan) significantly improves professional responsibility, documentation honesty, service fairness, empathy, and comprehensive nurse performance. Implementing these spiritual values is proven to reduce moral conflict among nurses, increase patient satisfaction, and strengthen a humanistic, spiritually oriented work culture. Conclusively, an Islamic value-based nursing management ethics framework effectively enhances healthcare quality and patient safety, contributing significantly to achieving Sustainable Development Goal (SDG) 3.